2005
DOI: 10.1002/cne.20769
|View full text |Cite
|
Sign up to set email alerts
|

A proposed hypothalamic–thalamic–striatal axis for the integration of energy balance, arousal, and food reward

Abstract: We elaborate herein a novel theory of basal ganglia function that accounts for why palatable, energy-dense foods retain high incentive value even when immediate physiological energy requirements have been met. Basal ganglia function has been studied from the perspective of topographical segregation of processing within parallel circuits, with primary focus on motor control and cognition. Recent findings suggest, however, that the striatum can act as an integrated unit to modulate motivational state. We describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
288
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(314 citation statements)
references
References 120 publications
22
288
1
3
Order By: Relevance
“…The ability of scopolamine microinjections throughout medial shell to suppress hedonic reactions to sucrose, increase aversive 'disgust' reactions to bitter quinine, and suppress intake of palatable food is consistent with the hypothesis by Kelley et al (2005) that endogenous ACh signals in NAc shell promote food intake (potentially by enhancing palatability). Their ACh-appetite hypothesis arose from the original demonstrations that scopolamine microinjections into NAc suppressed food intake, and that NAc scopolamine microinjections also could serve as an unconditioned stimulus to induce conditioned avoidance of either a paired taste or a paired place (Pratt and Kelley, 2004;Pratt et al, 2007).…”
Section: Scopolamine Causes a Shift Toward Negative Affect And Motivasupporting
confidence: 71%
“…The ability of scopolamine microinjections throughout medial shell to suppress hedonic reactions to sucrose, increase aversive 'disgust' reactions to bitter quinine, and suppress intake of palatable food is consistent with the hypothesis by Kelley et al (2005) that endogenous ACh signals in NAc shell promote food intake (potentially by enhancing palatability). Their ACh-appetite hypothesis arose from the original demonstrations that scopolamine microinjections into NAc suppressed food intake, and that NAc scopolamine microinjections also could serve as an unconditioned stimulus to induce conditioned avoidance of either a paired taste or a paired place (Pratt and Kelley, 2004;Pratt et al, 2007).…”
Section: Scopolamine Causes a Shift Toward Negative Affect And Motivasupporting
confidence: 71%
“…60 In addition to DA, opioids and the MOR in particular are important in reward of palatable foods. 61,62 Through the work in our laboratory, we were the first to show that consumption of a high-fat diet could downregulate the expression of the MOR within reward circuitry structures. In mice that chronically consume a high-fat diet (from 3 to 20 weeks of age), the MOR expression is decreased within the reward circuitry and unchanged in the hypothalamus.…”
Section: Postnatal Effects Of a High-fat Dietmentioning
confidence: 99%
“…A recent study showed that surges of endogenously released striatal ENK act as signals to overeat palatable foods (Difeliceantonio et al, 2012). Accordingly, with regard to food motivation, fluctuations in striatal ENK expression have been hypothesized to track short-term motivational contingencies associated with feeding (Kelley et al, 2005;Will et al, 2007). This model proposes that striatal ENK downregulation is the 'off-switch' that signals recent completion of feeding.…”
Section: Comparing the Effects Of Sleep Deprivation And Food Deprivationmentioning
confidence: 99%